Training in Evidence-Based Practices Increases Likelihood to Integrate Different HIV Prevention Services with Substance-Using Clients. Issue 3 (3rd April 2018) - Pinto, Rogério M.; Spector, Anya Y.; Witte, Susan S.; Filippone, Prema; Choi, C. Jean; Wall, Melanie
ABSTRACT: Providers of social and public health services ("providers") often use HIV prevention strategies with substance-using clients to decrease HIV transmission and infection. This article examines factors that facilitate providers' use of select HIV-prevention strategies. Sample comprises 379 providers from 36 agencies in New York City. Outcomes: sexual risk assessments; risk reduction counseling; condom demonstration; and referrals to HIV testing. Predictors: training; job satisfaction; staff collaboration. The authors used multilevel logistic regression and linear multilevel models. HIV prevention training was associated with increased performance of each outcome. The odds of conducting several outcomes were higher for providers trained in evidence-based interventions. Staff collaboration and job satisfaction were associated with provision of multiple outcomes. This study shows training and collaboration/satisfaction as significantly influencing providers to use prevention strategies. Providers ought to be trained in multiple modalities, and agencies ought to prioritize collaborative environments that promote job satisfaction.